European public perceptions of homelessness: A knowledge, attitudes and practices survey - Petit, Junie (2019)
Addressing Citizen's perspectives on homelessness is crucial for the design of effective and durable policy responses, and available research in Europe is not yet substantive. We aim to explore citizens' opinions about homelessness and to explain the differences in attitudes within the general population of eight European countries: France, Ireland, Italy, the Netherlands, Poland, Portugal, Spain, and Sweden.